Implementation of Teaching Materials Based on Indonesian Culture in BIPA Learning As One Way to Lift Indonesian Culture in the World - Cahyani, I; Hadianto, D (KnE Social Sciences, 2018)
This study aims to develop various teaching materials as well as lifting Indonesian culture through bringing the learning of the Indonesian language to the eyes of the world through BIPA learning. The method used in this research is research and development. Researchers create teaching materials using various cultural terms from various regions in Indonesia, try them out with BIPA learners and make improvements to their shortcomings. The cultural materials used by the author in the mid-level BIPA textbook are a habit, a character from the area, traditional food, traditional clothing, rituals/ traditions, traditional dance, and traditional musical instruments. The results of this study indicated that the authors created unique BIPA teaching materials at intermediate level (B2) and succeeded in making BIPA learners more interested in learning Indonesian. In this way, learners can not only learn BIPA in terms of the Indonesian language but can also simultaneously get to know the culture of Indonesia. Keywords: instructional BIPA materials, intermediate level (B2), learning BIPA, terms in Indonesian culture